2018
DOI: 10.1111/are.13944
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clove ( Eugenia caryophyllus ) and cinnamon ( Cinnamomum zeylanicum ) essential oils in Nile tilapia diets on performance, antioxidant power and lipid oxidation in fillets

Abstract: This study evaluated the addition (0.35 and 0.70 g/kg feed) of clove (EOcl) or cinnamon (EOci) essential oils to Nile tilapia feed for 45 days to assess animal performance, antioxidant capacity and lipid oxidation in fillets. The design was completely randomised with five treatments and three replicates. Antioxidant capacity was determined by the oxygen radical absorbance capacity (ORAC FL ), 2,2-diphenyl-1picrylhydrazylhydrate (DPPH), ferric reducing ability power (FRAP) and 2,2'-azino-bis (3-ethylbenzothiazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…Another possible explanation for the decrease in MDA is that the antioxidant compounds of cinnamon essential oil entered the circulatory system and accumulated in fillets (Botsoglou et al., 2002). These results indicated that the cinnamon essential oils had an effect on lipid oxidation, which was beneficial to the balance between prooxidants and antioxidants, thus preventing oxidation (Sary et al., 2018). In addition, Fernández et al.…”
Section: Resultsmentioning
confidence: 98%
“…Another possible explanation for the decrease in MDA is that the antioxidant compounds of cinnamon essential oil entered the circulatory system and accumulated in fillets (Botsoglou et al., 2002). These results indicated that the cinnamon essential oils had an effect on lipid oxidation, which was beneficial to the balance between prooxidants and antioxidants, thus preventing oxidation (Sary et al., 2018). In addition, Fernández et al.…”
Section: Resultsmentioning
confidence: 98%
“…besides the antibacterial and antioxidant action, can be an important alternative for food preservation and flavor. reducing the concentration of synthetic additives in these products (Guerrero et al, 2018;Monteschio et al, 2017;Rivaroli et al, 2016;Sary et al, 2021a;Vital et al, 2018a, b).…”
Section: Consumer Acceptability Of Infant Food With Oregano Essencial...mentioning
confidence: 99%
“…Estudos anteriores concentraram-se nos compostos isolados de cada planta (Guerrero et al, 2018;Ornaghi et al, 2017;Sary et al, 2019) ou, em alguns casos, em misturas de metabólitos secundários de plantas (Cruz et al, 2014;Fugita et al, 2018; Research, Society and Development, v. 10, n. 8, e4210816900, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i8.16900 Monteschio et al, 2017Monteschio et al, , 2019Souza et al, 2019). O uso de uma mistura de metabólitos secundários pode potencializar o sinergismo dos compostos finais.…”
Section: Introductionunclassified